Emprego do imageamento elétrico no estudo da contaminação por cemitérios - Silva, Robson Willians da Costa; Malagutti Filho, Walter [UNESP] (My University, 2010)
Due to lack of environmental protection with which the process of burying the corpses was conducted over the decades, many cemeteries have become areas contaminated by organic and inorganic substances and pathogenic microrganisms. This paper presents the results of electrical imaging in delineation of areas potentially contaminated by necrochorume in the municipal cemetery of Vila Rezende, Piracicaba - SP. The results indicate a depth of water table among 3,1 and 5,1 m, with two flow directions, being one to SW and another to SE. So the probable contamination plume, that has the same directions of underground flow, as for the conductive anomalies verified at the geoelectrics sections confirm the suspicions of contamination in the area. The probable plume the SE is prolonged to out of the cemetery. The location of the conductive anomalies and likely contamination plumes demonstrated that the contamination is linked with the depth of water table level and the burial time.

Devido à falta de proteção ambiental com a qual o procedimento de enterrar os corpos foi conduzido ao longo das décadas, muitos dos cemitérios se tornaram áreas contaminadas, por substâncias orgânicas e inorgânicas, e microrganismos patogênicos. Neste trabalho são apresentados os resultados do imageamento elétrico na delimitação de áreas potencialmente contaminadas por necrochorume, no cemitério municipal de Vila Rezende, Piracicaba - SP. Os resultados indicam uma profundidade do nível freático entre 3,1 e 5,1 m, com duas direções de fluxo subterrâneo, uma a SW e outra a SE. Tanto as prováveis plumas de contaminação, que tem as mesmas direções de fluxo subterrâneo, quanto às anomalias condutivas verificadas nas seções geoelétricas, confirmam as suspeitas de contaminação na área. A provável pluma a SE prolonga-se para fora dos limites do cemitério. A localização das anomalias condutivas e das prováveis plumas de contaminação demonstrou que a contaminação tem ligação com a profundidade do nível freático e com o tempo de sepultamento. Palavras-chave: imageamento elétrico, cemitério, necrochorume.
Application of electrical imaging in the study of contamination from cemeteries
Keywords: Cemetery; Electrical imaging; Necrochorume